Application of Sustainable Village Development in Bukalapak’s Advertisement the Series “Berkawan dengan Zaman” - Jastisia, Irenia; Yani, Aditya Rahman (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2022)
Rural communities are synonymous with the lack of welfare and are still lagging behind, so there is a need for community empowerment. Dilain side, Sustainable Development Goals (SDGs) is an international agenda in which Indonesia participates. Referring to the agenda, Bukalapak as one of the companies in Indonesia also made it happen through the advertisement series